2016
DOI: 10.1111/jace.14157
|View full text |Cite
|
Sign up to set email alerts
|

DC Electric Field‐Enhanced Grain‐Boundary Mobility in Magnesium Aluminate During Annealing

Abstract: Magnesium aluminate spinel was sintered and annealed at 1300°C under an applied 1000 V/cm DC electric field. The experiment was designed such that current could be removed as a variable and just the effect of a noncontact electric field was studied. Enhanced grain growth was observed for both samples that were sintered or annealed after densification in the presence of an electric field. Grain-boundary character distributions revealed that no microstructural changes were induced due to the field. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…47,48 Plotting cation distribution profiles as a function of normalized space coordination [ie, CS divided by the Debye length (L D )] ( Figure 4B) indicated the effect of grain size on charge distribution in nano-scale MAS. Maier 29,38 proposed that for ionic materials with grains smaller than four times the L D , the GC is no longer electrically neutral and the sample is considerably influenced by accumulation or depletion of charge at the boundaries. For the nonstoichiometric MAS studied in this work, the L D was estimated to range between 3.5 and 9.0 nm (Supplemental Material A.3 in Data S1).…”
Section: Cation Distribution and Lattice Orderingmentioning
confidence: 99%
See 2 more Smart Citations
“…47,48 Plotting cation distribution profiles as a function of normalized space coordination [ie, CS divided by the Debye length (L D )] ( Figure 4B) indicated the effect of grain size on charge distribution in nano-scale MAS. Maier 29,38 proposed that for ionic materials with grains smaller than four times the L D , the GC is no longer electrically neutral and the sample is considerably influenced by accumulation or depletion of charge at the boundaries. For the nonstoichiometric MAS studied in this work, the L D was estimated to range between 3.5 and 9.0 nm (Supplemental Material A.3 in Data S1).…”
Section: Cation Distribution and Lattice Orderingmentioning
confidence: 99%
“…Moreover, the use of EFs is associated with reductions in grain growth and flow stress in ionic materials . Rufner et al . reported that applying a DC electric field of 1000 V/cm at 1300°C enhanced grain‐boundary (GB) mobility in MAS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohan et al [51] also discussed Zr segregation at spinel grain boundaries (with addition of zirconia) limiting grain growth and grain boundary migration. On the other hand, Rufner et al [58] observed enrichment of Al at spinel-spinel grain boundaries (undoped spinel) resulting in reduced Mg/Al ratio at the interface. Nuns et al [59] also reported previously the enrichment of Al and O at spinel-spinel boundaries (in undoped sample) while Mg was found to be depleted.…”
Section: Qualitative Observations Of Elemental Segregation At Grain Boundariesmentioning
confidence: 99%
“…Majidi and co‐workers have employed in situ transmission electron microscopy (TEM) to demonstrate that non‐contacting electrostatic fields applied to partially stabilized ZrO 2 trigger modest densification at temperatures that do not lead to appreciable densification in the absence of any electric field . More recently, Rufner et al have reported field‐induced grain growth in MgAl 2 O 4 , while Rheinheimer et al confirmed similar findings for SrTiO 3 . Hughes and co‐workers have recently used bicrystals of (100) twist grain boundaries in SrTiO 3 to demonstrate that an applied electric field changes the atomic and electronic grain‐boundary core structures .…”
Section: Introductionmentioning
confidence: 99%